Reference meanings of the Group object - Sepúlveda-Delgado, Omaida; Suárez-Aguilar, Zagalo Enrique; Pino-Fan, Luis Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this article is to answer the question: What is the meaning of the mathematical object group? For this, the Ontosemiotic Approach to Knowledge and Mathematical Instruction is taken into account as a theoretical reference. In this direction, a synthesis of the reconstruction of the global meaning of the Group object and of the reference meanings given in two classic books (Herstein and Gallian) and in two contemporary books (Lezama and Caicedo) is presented, following the methodology of semiotic analysis. of texts, proposed by this approach. As results, the meanings of the Group object, both global and partial, are presented, identified in books where it is evident that these intend to arrive at work with the meaning "Abstract"; and problem-situations are proposed as a teaching strategy to promote the understanding of partial meanings identified in the epistemic configurations, emerging from the epistemological and historical study. The study of the meanings of this object is important in the design of the instruction to decide which of these are implemented in the instructional process through the mathematical practices that motivated its development.